2020
DOI: 10.1186/s12985-020-01304-2
|View full text |Cite
|
Sign up to set email alerts
|

The USP18 cysteine protease promotes HBV production independent of its protease activity

Abstract: Background: Hepatitis B virus (HBV) infection remains as one of the major public health problems in the world. Type I interferon (IFN) plays an essential role in antiviral defense by induced expression of a few hundred interferon stimulated genes (ISGs), including ubiquitin-specific protease 18 (USP18). The expression level of USP18 was elevated in the pretreatment liver tissues of chronic hepatitis B(CHB) patients who did not respond to IFN treatment. Thus, this study was designed to investigate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…-IFNα is without IFN-α treatment, and +IFNα is with IFN-α treatment. Data are presented as mean ± SD; Error bars indicate SD; **P < 0.01, ***P < 0.001. others and our laboratories showed that USP18 promotes HBV production by inhibiting the type I IFN signaling pathway (Li et al, 2016(Li et al, , 2020. Interestingly, it has been reported that cells developed IFN resistance following DENV infection.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…-IFNα is without IFN-α treatment, and +IFNα is with IFN-α treatment. Data are presented as mean ± SD; Error bars indicate SD; **P < 0.01, ***P < 0.001. others and our laboratories showed that USP18 promotes HBV production by inhibiting the type I IFN signaling pathway (Li et al, 2016(Li et al, , 2020. Interestingly, it has been reported that cells developed IFN resistance following DENV infection.…”
Section: Discussionmentioning
confidence: 75%
“…Similar findings were reported in pre-treatment liver tissues of patients chronically infected with HBV ( Xiao et al, 2012 ). Previous work from others and our laboratories showed that USP18 promotes HBV production by inhibiting the type I IFN signaling pathway ( Li et al, 2016 , 2020 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Additionally, USP18 dampens the effects of type I and type III IFNs by exerting negative feedback control through its regulatory role (89). Moreover, USP18 also binds to and deubiquitinates TAK1, thereby promoting hepatic inflammatory responses (90)(91)(92).…”
Section: Viral Hepatitismentioning
confidence: 99%
“…ISGF3 translocates to the nucleus, where it binds to the ISRE and induces the expression of a few hundred ISGs to exert their antiviral or pro-viral activity. [6][7][8][9] The UMP-CMP kinase 2 (CMPK2) has recently been reported to be associated with virus infection and host antiviral response.…”
mentioning
confidence: 99%